Risk of deterioration among general ward patients: Nurses’ ability in assessing early warning signs - Mohamed Ludin, Salizar (Lincoln University College Kuala Lumpur, Malaysia, 2018)
Background The challenge of recognizing ward-based patients at risk of deterioration is discussed frequently within the relevant literature. Nurses in particular hold the prime position to identify problems at an early stage using systematic patient assessment. However, general ward nurses’ perceived knowledge, attitudes, and practice related to assessment of the risk of deterioration are not well understood. Failures to recognize or act upon the deterioration of general ward patients has sometimes resulted in the implementation of early warning scoring systems and Critical Care Outreach teams. Aim: The study aim to explore general ward nurses’ perceived knowledge, attitude, and practice (KAP) in assessing patients at risk of deteriorating in general wards. Method A Cross-sectional study design with Modified Early Warning Score questionnaire for general ward nurses was done in one tertiary hospital in Malaysia in 2013 and 2014. Results: General ward nurses perceived that they struggled with knowledge and attitude, but they feel they performed good practice in assessing patients at risk for deterioration. Nevertheless, the study finding shows otherwise. Only one respondent achieved ‘grade B’ (85%) and the remainder scored in the band ‘grade F’ (very poor). The respondents’ attitude was measured by their perception of their levels of confidence and concern. The mean confidence level was greater than six out of 10 for all categories. The attitudes mean score ± SD was set at 42.02 ±7.76. The data showed that 51% (N=50) scored below mean core of 42.02. However, participants’ overall mean score ±SD for perceptions of practice (risk of deterioration assessment) was 90.27 ± 21.87 (6.94+/-1.683). The majority of participants awarded themselves a score between eight and nine, which is in the ‘good’ range for the scale (0-2 weak; 3-5 moderate; 6-8 good; 9-10 excellent). Those who scored above it were classified as having a good attitude. Conclusion: A need exists for general ward nurses to gain a knowledge foundation in detecting abnormality to address lack of confidence, poor attitude and alertness, and concern.